1994
DOI: 10.7748/ns.8.15.32.s40
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord care in pre-term babies

Abstract: A trial was undertaken to investigate infection rates and to measure cord separation time under four different cord care regimes in pre-term babies within the Neonatal Unit of Ninewells Hospital, Dundee. The evidence of the trial suggests that the present method of treating umbilical cords in pre-term babies with Sterets and Ster-zac powder is sound. More importantly, there is good evidence that a policy of leaving umbilical cords untreated cannot be recommended as safe practice within the unit. It is noted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…5 In this study dry cord care was performed from the first nappy change cleansing the UC with sterile saline solution (NaCl 90%), using a sterile gauze twice a day, and left without any dressing upon it as well. The research, confirming data shown in other trials conducted in healthy term infants born in high-income or middle-income hospital setting, 2,[15][16][17] found no difference in occurrence of UC AEs between the two groups, that also did not have statistically significant differences in percentages distribution of baseline characteristics of newborns (type of delivery, birth weight, parenthood order, sex, breastfeeding at discharge and at home) and of mothers (age, education).…”
Section: Resultssupporting
confidence: 77%
“…5 In this study dry cord care was performed from the first nappy change cleansing the UC with sterile saline solution (NaCl 90%), using a sterile gauze twice a day, and left without any dressing upon it as well. The research, confirming data shown in other trials conducted in healthy term infants born in high-income or middle-income hospital setting, 2,[15][16][17] found no difference in occurrence of UC AEs between the two groups, that also did not have statistically significant differences in percentages distribution of baseline characteristics of newborns (type of delivery, birth weight, parenthood order, sex, breastfeeding at discharge and at home) and of mothers (age, education).…”
Section: Resultssupporting
confidence: 77%
“…210 Studies which applied nothing to the cord had mean separation times of about 9 days. 14,24,25 Meta-analysis of 4 studies with alcohol as the comparator showed a trend toward cord separation being significantly prolonged in the alcohol group but there was no significant difference in cord separation, 1 while the present study showed a statistical difference between the 2 groups: in DCC the mean UC separation time was about 2 days before of control group 1 (10 days vs 12 days). The clinical impact of delays of cord separation is unknown, but it has social and cost implications: delay makes mothers anxious, and it increases the number of domiciliary midwife visits to the home.…”
Section: Discussioncontrasting
confidence: 51%
“…It confirms data shown in other trials conducted in healthy term infants born in high-income or middle-income hospital setting. 2,15,16 …”
Section: Discussionmentioning
confidence: 99%
“…A thorough hand-washing constitutes an important measure in the prevention of cord stump contamination [2,3], but the tendency of medical and paramedical attendants to perform this simple hygienic procedure is notoriously low [4,5]. This is the reason why several authors recommend the application of an antiseptic on the UC [6][7][8]. Although the American Academy of Pediatrics considers no antiseptic treatment to be superior to any other, they confirm its utility [9].…”
Section: Introductionmentioning
confidence: 99%